2021
DOI: 10.1002/oby.23311
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of endothelial dysfunction in noncritically ill hospitalized COVID‐19 patients: A cross‐sectional study

Abstract: Objective The aim of this study was to identify determinants of endothelial dysfunction in patients hospitalized with acute COVID‐19. Methods A total of 109 hospitalized COVID‐19 patients in noncritical status were cross‐sectionally studied. Clinical data (age, sex, comorbidities, and medications) and BMI were assessed. Laboratory tests included serum hemoglobin, leukocytes, lymphocytes, platelets, C‐reactive protein, ferritin, D‐dimer, and creatinine. Physical status was evaluated using a handgrip dynamometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…To our knowledge, this is the largest study extensively investigating the association between bFMD, a potential clinical and non-invasive measure of endothelial function, and in-hospital outcomes of COVID-19 patients. Indeed, in some recent studies in which bFMD was evaluated in patients with recent or ongoing COVID-19, the association between bFMD and the in-hospital prognosis of enrolled patients was not assessed [25][26][27]. In addition, a recent observational study involving 98 patients with confirmed COVID-19 investigated only the prospective association between bFMD and in-hospital mortality [28].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest study extensively investigating the association between bFMD, a potential clinical and non-invasive measure of endothelial function, and in-hospital outcomes of COVID-19 patients. Indeed, in some recent studies in which bFMD was evaluated in patients with recent or ongoing COVID-19, the association between bFMD and the in-hospital prognosis of enrolled patients was not assessed [25][26][27]. In addition, a recent observational study involving 98 patients with confirmed COVID-19 investigated only the prospective association between bFMD and in-hospital mortality [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, even under adequate medical treatment, pneumonia caused by SARS-CoV-2 infection may cause an injury to the lung parenchyma, with permanent structural damage (3). Studies have also shown a direct relationship between COVID-19 and poor cardiovascular outcomes, such as increased arterial stiffness, and an association between overweight and endothelial dysfunction (4)(5)(6)(7). Initial investigations showed that SARS-CoV-2 is able to infect the endothelial cells, which are responsible for regulating vascular tone (8) harming the vascular function of these individuals (6).…”
mentioning
confidence: 99%
“…Seventeen studies have examined the association of COVID‐19 with endothelial function. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Notably, it should be acknowledged that of the 16 studies assessing endothelial dysfunction through FMD, only four studies clearly adjusted FMD measurement for shear stress indices. Τhus, residual confounding regarding the association between endothelial dysfunction and outcomes in acute and post‐recovery COVID‐19 cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Increased body mass index and renal disease have been both associated with endothelial dysfunction in noncritically hospitalized patients with COVID‐19. 18 Additionally, patients with type 2 diabetes and under treatment with beta blockers or angiotensin receptor blockers (ARBs) presented significantly lower FMD values. 14 Importantly, higher values of interleukin‐6 and troponin I during hospitalization were also associated with impaired endothelial function at the acute phase.…”
Section: Discussionmentioning
confidence: 99%